Historical Context of Cardiac Rehabilitation: Learning From the Past to Move to the Future - Redfern, Julie; Gallagher, Robyn; O’Neil, Adrienne; Grace, Sherry L.; Bauman, Adrian; Jennings, Garry; Brieger, David; Briffa, Tom (Frontiers in Cardiovascular Medicine, 2022)
Contemporary myocardial infarction (MI) care and management has evolved dramatically since the 1950’s; yet outpatient rehabilitation remains underutilized. Deepening our understanding of the origins and history of cardiac rehabilitation highlights a contemporary shift required for policy and practice related to secondary prevention of coronary disease in light of societal changes as well as medical, digital and surgical advancements. Contemporary “cardiac rehabilitation” began when bed rest and physical inactivity was recommended and commonplace for MI survivors. Today, most patients who survive an MI, undergo reperfusion therapy, a short inpatient stay and are discharged with minimal physical morbidity. Despite this, the majority of modern day programs continue to be structured in the same way they have been for the past 50 years and this model has become incongruent with the contemporary context, especially in the COVID-19 era. This review aims to describe the historical foundations of cardiac rehabilitation to inform solutions and meet the demands of contemporary MI management. Delivering health systems reform to address modernization is current healthcare challenge where a united and interdisciplinary effort is needed.